Hubungan Tingkat Pengetahuan dan Dukungan Keluarga Terhadap Kepatuhan Pasien Gangguan Jiwa dalam Mengonsumsi Obat di Wilayah Kerja Puskesmas Telaga - Firmawati Firmawati; Andi Nur Aina Sudirman; Tika Agustuti Sapeni (Jurnal Medika Nusantara, 2023)
The problem of mental disorders throughout the world has become a severe problem. One of the factors for the recurrence of mental disorders is compliance with medication. Patient knowledge, family support, drug side effects, therapeutic relationships, and disease characteristics influence compliance with taking patient medication. The study aimed to determine the relationship between the levels of knowledge with family support on the compliance of patients with mental disorders in taking medication. The research design used a quantitative analytic study with a cross-sectional approach—the sampling using Total sampling, totalling 32 respondents. The statistical test used the Chi-Square test, the p-value of the level of knowledge with compliance is 0.0001, and the p-value of family support with compliance is 0.015 with ? <0.05. It can conclude that there is a significant relationship between the level of knowledge and family support on patients' compliance with mental disorders in taking medication. It hopes that a high level of family knowledge and family support can increase patient compliance in taking medication.